2014
DOI: 10.1213/ane.0000000000000387
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Statin Administration Does Not Protect Against Early Postoperative Acute Respiratory Distress Syndrome

Abstract: Background Statins have been shown to possess anti-inflammatory and immunomodulatory effects. The objective of this study was to determine if preoperative statin therapy is associated with a reduced frequency of postoperative ARDS in surgical populations at increased risk of developing ARDS. Methods We performed a retrospective cohort evaluation of the association between preoperative statin therapy and early postoperative ARDS in patients undergoing elective high-risk thoracic and aortic vascular surgery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…But it should be interpreted with caution, because of the significant heterogeneity in included studies. Our finding was consistent with the conclusions of the only RCT and a recent study by Yadav et al . However, a previous study, covering 575 ICU patients, indicates that the prevalence of ALI/ARDS is lower in patients receiving prior statin therapy than in non‐statin group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…But it should be interpreted with caution, because of the significant heterogeneity in included studies. Our finding was consistent with the conclusions of the only RCT and a recent study by Yadav et al . However, a previous study, covering 575 ICU patients, indicates that the prevalence of ALI/ARDS is lower in patients receiving prior statin therapy than in non‐statin group.…”
Section: Discussionsupporting
confidence: 93%
“…Major characteristics of the included studies are summarized in Table . In general, the 13 studies, including four RCTs and nine cohort studies, were published between 2007 and 2015 covering a total of 12 145 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of statins on respiratory or infectious complications in medical patients are controversial, with limited data in the perioperative setting. Le Manach et al30 reported no difference in postoperative pneumonia in a vascular cohort, and Yadav et al33 reported no difference in rates of early postoperative adult respiratory dis-…”
mentioning
confidence: 98%
“…66 Although animal and preliminary human studies had also suggested statins may have a preventive role in ARDS, a randomized controlled trial of 540 patients and other observational studies have been disappointing. [67][68][69] Other proposed potential therapies for ARDS prevention include angiotensin inhibitors, curcumin, 70 peroxisome proliferator receptor antagonist, 71,72 and adrenomodulin. 73…”
Section: Systemic Therapiesmentioning
confidence: 99%